2004
DOI: 10.1152/ajpheart.00620.2003
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of neuronal nicotinic ACh receptors in rat microvascular endothelial cells

Abstract: The expression and function of nicotinic ACh receptors (nAChRs) in rat coronary microvascular endothelial cells (CMECs) were examined using RT-PCR and whole cell patch-clamp recording methods. RT-PCR revealed expression of mRNA encoding for the subunits alpha(2), alpha(3), alpha(4), alpha(5), alpha(7), beta(2), and beta(4) but not beta(3). Focal application of ACh evoked an inward current in isolated CMECs voltage clamped at negative membrane potentials. The current-voltage relationship of the ACh-induced curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 28 publications
4
43
0
Order By: Relevance
“…7) Amounts of the a5 and a7 transcripts in BBMEC may not reach the detectable level in the present condition. On the other hand, slightly different expression patterns have been reported in rat coronary microvascular endothelial cells (a2, a3, a4, a5, a7, b2 and b4 subunits) 22) and in human aortic endothelial cells (a3, a5, a7, b2 and b4 subunits). 5,6) In contrast to the cerebral endothelial cells, these peripheral endothelial cells seem to express the b4-containing nicotinic receptor which is less sensitive to desensitization than the b2-containing and the a7-containing nicotinic receptors.…”
Section: Discussionmentioning
confidence: 88%
“…7) Amounts of the a5 and a7 transcripts in BBMEC may not reach the detectable level in the present condition. On the other hand, slightly different expression patterns have been reported in rat coronary microvascular endothelial cells (a2, a3, a4, a5, a7, b2 and b4 subunits) 22) and in human aortic endothelial cells (a3, a5, a7, b2 and b4 subunits). 5,6) In contrast to the cerebral endothelial cells, these peripheral endothelial cells seem to express the b4-containing nicotinic receptor which is less sensitive to desensitization than the b2-containing and the a7-containing nicotinic receptors.…”
Section: Discussionmentioning
confidence: 88%
“…The presence of ␣ and ␤ subunits not previously reported to be expressed in adrenal medullary tissue could reflect a unique fetal pattern of expression. As a word of caution in interpreting these findings, the presence of vascular components such as endothelial cells, vascular smooth muscle, and cortex in the tissue preparation could contribute to the detection of these subunits (30). The decreased expression of nicotinic receptor subunits in the LTH fetal adrenal implicates a decreased capacity to respond to cholinergic stimuli as a potential mechanism leading to the decreased expression of all three enzymes mediating catecholamine synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular mechanisms that are activated by nicotine in endothelial cells have been demonstrated by Di Luozzo et al 109 and include MAPKs p38 and p44/p42. The receptors present on rat endothelial cells, as revealed 110 by RT-PCR include nAChRs a 2, a 3, a 4, a 5, a 7, b 2, and b 4 but not b 3. Saeed et al 111 have demonstrated that nicotine inhibits the expression of endothelial adhesion molecules, suggesting that the effect of nicotine on these cells is anti-infl ammatory.…”
Section: Endotheliummentioning
confidence: 97%